Effect of carbohydrate or carbohydrate plus medium chain triglyceride ingestion on cycling time trial performance - Angus, D. J.; Hargreaves, M.; Dancey, J.; Febbraio, M. A. (Journal of Applied Physiology, 2000)
This study examined the effectiveness of ingesting a carbohydrate or carbohydrate + medium-chain triglycerides (MCT) on metabolism and cycling performance. Eight endurance-trained men [peak O(2) uptake = 4.71 +/- 0.09 (SE) l/min] completed 35 kJ/kg as quickly as possible [time trial (TT)] while consuming 250 ml/15 min of either a 6% (wt/vol) carbohydrate solution (C), a 6% carbohydrate + 4.2% MCT solution (C+M), or a sweet placebo (P). Time to complete the set amount of work was reduced in both C and C+M compared with P by 7 and 5%, respectively (C: 166 +/- 7 min; C+M: 169 +/- 7 min; P: 178 +/- 11 min; P < 0.01). Plasma glucose concentration was maintained at or above resting values throughout both C and C+M trials but decreased (P < 0.05) below resting values in P at the completion of the TT. The estimated rate of carbohydrate oxidation was not different during the first 90 min of exercise but thereafter was reduced (P < 0.05) in P and was maintained in both C and C+M. These data demonstrate that carbohydrate ingestion during exercise improves 100-km TT performance compared with a sweet placebo, but the addition of MCT does not provide any further performance enhancement.